Beyond International Aid: The Strategy of Local NGOs in Post-Disaster Community Economic Empowerment in Aceh - Muhammad Asief Alizarzady (Winaya Inspirasi Nusantara Foundation, 2027)
Following the 2004 Indian Ocean Tsunami, the scale of international aid that flowed into Aceh exposed a structural problem instead of solving one. Assistance concentrated in areas that were physically accessible, while many rural communities remained underserved, producing new inequalities rather than an even recovery. This gap opened space for local civil society organizations to take on roles that neither the state nor international agencies had filled. This study examines how Forum Bangun Aceh (FBA), a Banda Aceh based local NGO, strategized community empowerment through its Economic Empowerment program between 2005 and 2019. Using a qualitative case study approach built on systematic document analysis, the study applies Friedmann's (1992) three-dimensional empowerment framework, enabling, empowering, and protecting, to trace how FBA's programs evolved over fifteen years. The findings show that FBA's strategy coherently spans all three dimensions: enabling through post-disaster recovery and disaster risk reduction education, empowering through micro credit, cooperative formation, and skills training rooted in local economic practices, and protecting through multi-stakeholder engagement and advocacy for persons with psychosocial disabilities. These findings carry two implications. Theoretically, they support the argument that empowerment interventions anchored in local value systems tend to outlast those designed externally. Practically, they offer local NGOs and policymakers a working model for sequencing recovery, capacity building, and advocacy without relying on the scale of international actors.